Publishing Shakespeare in India: Macmillan’s English Classics and the Aftereffects of a Colonial Education - Mannan, Joya (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
India’s rejection of Macmillan’s English Classics series constitutes an important counter-origin that exposes and dismantles underlying assumptions about how colonial Indian readers valued and consumed Shakespeare. In this paper, I examine the failure of Macmillan’s English Classics series to bring about Indian assimilation to British values. I specifically consider Kenneth Deighton’s Shakespeare editions in the series and argue that Deighton’s Shakespeare attempted to utilize its extensive explanatory notes as a primer on Englishness for Indians. The pedantic notes, as well as the manner in which the texts were appropriated into Indian educational systems, were determining factors in their ultimate failure to gain widespread popularity in the colony. The imperial agenda that insists upon one dominant, valid discourse led to Macmillan misreading the market and misreading an already viable field of Shakespeare studies in India. Reflecting on narratives and histories surrounding the origins of Shakespeare studies in India, as well as how Shakespeare’s works were produced for the colonies and the way in which they were duly rejected, reveals how exchanges of power and capital between metropole and colony shape Western systems just as heavily as they do others.